Trends in the prevalence and care-seeking behaviour for acute respiratory infections among Ugandan infants - Sanni Yaya; Ghose Bishwajit (BMC, 2019)
Abstract Background Acute Respiratory Infections (ARIs) as a group of diseases/symptoms constitute a leading cause of pediatric morbidity and mortality in sub-Saharan Africa where over 10 % of all children die before reaching their fifth birthday. Although the burden of ARIs is highest in the African countries, there is little evidence in the current literature regarding their prevalence and treatment seeking. The objective of this study was therefore to assess the secular trend in the prevalence of ARIs as well as their treatment seeking-behaviour among Ugandan infants. Methods This cross-sectional study was based on data from Uganda Demographic and Health Surveys (conducted between 1995 and 2016) on 26,974 singleton infants aged 0-5 months. Mothers (aged 15-49 years) were interviewed to collect information on the prevalence of recent occurrences of fever, cough and dyspnea. The adjusted trend in the prevalence and predictors of ARIs and care seeking were measured by multivariate regression methods. Results In 2016, the prevalence of fever, cough and dyspnea was respectively 36.23, 42.55 and 19.27%. The prevalence of all three symptoms has been declining steadily since 1995, and the percentage of children receiving treatment for fever/cough has also more than doubled during the same time. In multivariable analysis, several sociodemographic factors emerged as significant predictors of ARIs including child's age and high birth order, mother's age, educational level, occupation, intendedness status of the child, BMI, household wealth status, and place of residency. Conclusions The overall prevalence common ARIs (fever, cough, dyspnea) has been declining at a slow but steady rate, however, remains noticeably high in comparison with countries with similar level of per capita GDP in Africa. Findings of this study has important implications for health policy making regarding the prevention of ARIs among infants in the country.